2020
DOI: 10.3390/pathogens9030197
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Lassa Fever

Abstract: Lassa virus (LASV), the causative agent of Lassa fever, is estimated to be responsible for up to 300,000 new infections and 5000 deaths each year across Western Africa. The most recent 2018 and 2019 Nigerian outbreaks featured alarmingly high fatality rates of up to 25.4%. In addition to the severity and high fatality of the disease, a significant population of survivors suffer from long-term sequelae, such as sensorineural hearing loss, resulting in a huge socioeconomic burden in endemic regions. There are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 63 publications
(316 reference statements)
0
41
0
Order By: Relevance
“…Indeed, several laboratories have used LCMV to develop surrogate animal models for LF (reviewed in [19]). For example, the LCMV (WE strain) can cause a disease in rhesus macaques [20] and HHD mice [21] that reproduces certain aspects of LASV pathogenesis such as vascular leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several laboratories have used LCMV to develop surrogate animal models for LF (reviewed in [19]). For example, the LCMV (WE strain) can cause a disease in rhesus macaques [20] and HHD mice [21] that reproduces certain aspects of LASV pathogenesis such as vascular leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, little has been known about the mechanisms of innate immunity in Mastomys and other natural rodent reservoirs of LASV, and an experimental system is lacking to directly address these important questions. Laboratory mice are of different rodent species and do not persistently shed virus upon LASV infection ( [58], reviewed in [19]). As such, we are unable to determine whether LASV Z inhibits innate immunity of their natural rodent hosts in a similar manner or mechanism as seen in humans and whether and how strain variations of the Z protein or other viral proteins may affect LASV interactions within the natural rodent hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal models have been developed to characterize the degrees of viral virulence and disease pathology mediated by LASV infection (reviewed in [19]). Accumulating evidence has suggested that different LASV isolates can mediate differential degrees of virulence and disease pathogenesis in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…While different animal species have been developed as animal models of LF [4], they all have certain constraints. For example, the use of NHPs, such as marmosets or rhesus macaques, can incur exorbitant expenses of high containment BSL4 facilities and experienced lab personnel (veterinarians) needed to conduct LASV studies.…”
Section: Discussionmentioning
confidence: 99%
“…The description of different animal models of LF has recently been reviewed elsewhere [4]. Each of the known LF animal models has its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%